Kagami‐Ogata syndrome: an important differential diagnosis to Beckwith‐Wiedemann syndrome. Issue 4 (28th January 2020) - Altmann, Judith; Horn, Denise; Korinth, Dirk; Eggermann, Thomas; Henrich, Wolfgang; Verlohren, Stefan
Abstract: We report the case of a fetus with sonographic characteristics of Beckwith‐Wiedemann syndrome (BWS). A 30‐year‐old gravida 2 para 1 was referred to our fetal medicine unit with an omphalocele. Fetal macrosomia, organomegaly, and polyhydramnios but no macroglossia were detected and BWS was suspected. Genetic testing for BWS did not confirm the suspected diagnosis as the karyotype was normal. Symptomatic polyhydramnios led to repeated amnioreductions. At 35 + 5 weeks of gestation, a female neonate of 3660 g was delivered with APGAR scores of 6/7/8, after 1/5/10 min, respectively. The abnormal shape of the thorax, facial dysmorphism, need for ventilation, and generalized muscular hypotonia led to the suspicion of Kagami‐Ogata syndrome (KOS), which was confirmed by genetic testing. KOS in our patient was caused by a large deletion in the MEG3‐region on chromosome 14q32 affecting the maternal allele. In this report, we highlight the notion that when sonographic signs suggestive of BWS such as macrosomia, polyhydramnios, and omphalocele are present and genetic testing does not confirm the suspected diagnosis, KOS should be tested for.